Does Magnetic Resonance Imaging Grading Correlate With Return to Sports After Bone Stress Injuries? A Systematic Review and Meta-analysis. Issue 3 (March 2022) - Hoenig, Tim; Tenforde, Adam S.; Strahl, André; Rolvien, Tim; Hollander, Karsten
Background: While some studies have failed to reveal any significant relationship between magnetic resonance imaging (MRI) grading and return to sports after bone stress injuries, others have reported either a linear or nonlinear relationship. Purpose: To evaluate the prognostic value of MRI grading for time to return to sports and rate of return to sports after bone stress injuries. Study Design: Systematic review and meta-analysis. Methods: A systematic search was performed in PubMed, Web of Science, SPORTDiscus, and Google Scholar. Studies reporting return to sports data after bone stress injuries using MRI grading systems were included in this review. The risk of bias was evaluated using the Quality in Prognosis Studies tool. Meta-analyses were performed to summarize the mean time to return to sports. The Pearson correlation was used to determine the relationship between time to return to sports and MRI grade. A meta-analysis of proportions was conducted to determine the percentage of athletes who successfully returned to sports. Results: A total of 16 studies with 560 bone stress injuries met inclusion criteria. Higher MRI-based grading was associated with an increased time to return to sports ( P < .00001). Pooled data revealed that higher MRI-based grading correlated with a longer time to return to sports ( r = 0.554; P = .001). Combining all anatomic locations, the mean time to return to sports was 41.7 days (95% CI, 30.6-52.9), 70.1 days (95% CI, 46.9-93.3), 84.3 days (95% CI, 59.6-109.1), and 98.5 days (95% CI, 85.5-112.6) for grade 1, 2, 3, and 4 injuries, respectively. Trabecular-rich sites of injury (eg, pelvis, femoral neck, and calcaneus) took longer to heal than cortical-rich sites of injury (eg, tibia, metatarsal, and other long-bone sites of injury). Overall, more than 90% of all athletes successfully returned to sports. Conclusion: The findings from this systematic review indicate that MRI grading may offer a prognostic value for time to return to sports after the nonsurgical treatment of bone stress injuries. Both MRI grade and location of injury suggest that individually adapted rehabilitation regimens and therapeutic decisions are required to optimize healing and a safe return to sports.